Annual Winter Site Fidelity of Barrow's Goldeneyes in the Pacific. Issue 1 (17th October 2019) - Willie, Megan; Esler, Daniel; Boyd, W. Sean; Bowman, Timothy; Schamber, Jason; Thompson, Jonathan
ABSTRACT: Coastal regions on the Pacific north coast of North America provide important wintering habitat for many species of sea ducks. Although winter range and habitat preferences are well described for most species, fidelity to coastal wintering sites is generally undocumented. Fidelity is an important factor necessary for understanding interactions with coastal developments and activities and corresponding management strategies. We used data from Barrow's goldeneyes ( Bucephala islandica ), a sea duck that winters predominantly in nearshore habitats along the Pacific north coast, to investigate inter‐annual fidelity to, and intra‐annual fidelity within, coastal wintering sites. Between 2006 and 2015, we marked goldeneyes on breeding, molting, and wintering sites with satellite transmitters. We retained 4, 931 locations in coastal habitats from 221 goldeneyes across 4 coastal regions for our analyses. These birds demonstrated high inter‐annual fidelity to coastal wintering sites; 75% of selected wintering sites were within 29 km of sites used the previous winter. Inter‐annual fidelity to wintering sites was similar between sex and age classes but differed by coastal region. Goldeneyes from southcentral Alaska, USA, expressed greater inter‐annual fidelity relative to birds from northern or southern British Columbia, Canada, and southeast Alaska. Goldeneyes also expressed high intra‐annual fidelity within wintering sites, with 75% of individuals averaging within‐season movements of ≤9 km. Intra‐annual fidelity was lesser for female than male goldeneyes but did not differ between hatch‐year and after‐hatch‐year birds. We found regional variation in intra‐annual fidelity, with goldeneyes from southcentral Alaska expressing greater intra‐annual fidelity compared to birds from other regions. High inter‐ and intra‐annual winter site fidelity by Barrow's goldeneyes suggests that, at a population level, habitat use is predictable and can be used to inform risk assessment or to evaluate factors affecting habitat choice. Also, low dispersal among wintering sites suggests that recovery from population perturbations, whether caused by natural or anthropogenic events, will be protracted. © 2019 The Wildlife Society. Abstract : High inter‐ and intra‐annual site fidelity by Barrow's goldeneyes along the Pacific north coast suggests that, at a population level, habitat use is predictable and can be used for assessing risks or to evaluate factors affecting habitat choice. Low dispersal of goldeneyes among wintering sites suggests that recovery from population perturbations, whether caused by natural or anthropogenic events, will be protracted.